A role for prolyl hydroxylase domain proteins in hippocampal synaptic plasticity - Corcoran, Alan; Kunze, Reiner; Harney, Sarah C.; Breier, Georg; Marti, Hugo; O'Connor, John J. (Hippocampus, 2013)
Hypoxia-inducible factors (HIFs) are key transcriptional regulators that play a major role in oxygen homeostasis. HIF activity is tightly regulated by oxygen-dependent hydroxylases, which additionally require iron and 2-oxoglutarate as cofactors. Inhibition of these enzymes has become a novel target to modulate the hypoxic response for therapeutic benefit. Inhibition of prolyl-4-hydroxylase domains (PHDs) have been shown to delay neuronal cell death and protect against ischemic injury in the hippocampus. In this study we have examined the effects of prolyl hydroxylase inhibition on synaptic transmission and plasticity in the hippocampus. Field excitatory postsynaptic potentials (fEPSPs) and excitatory postsynaptic currents (EPSCs) were elicited by stimulation of the Schaffer collateral pathway in the CA1 region of the hippocampus. Treatment of rat hippocampal slices with low concentrations (10 µM) of the iron chelator deferosoxamine (DFO) or the 2-oxoglutarate analogue dimethyloxalyl glycine (DMOG) had no effect on fEPSP. In contrast, application of 1 mM DMOG resulted in a significant decrease in fEPSP slope. Antagonism of the NMDA receptor attenuated the effects of DMOG on baseline synaptic signalling. In rat hippocampal slices pretreated with DMOG and DFO the induction of long-term potentiation (LTP) by tetanic stimulation was strongly impaired. Similarly, neuronal knockout of the single PHD family member PHD2 prevented murine hippocampal LTP. Preconditioning of PHD2 deficient hippocampi with either DMOG, DFO, or the PHD specific inhibitor JNJ-42041935, did not further decrease LTP suggesting that DMOG and DFO influences synaptic plasticity primarily by inhibiting PHDs rather than unspecific effects. These findings provide striking evidence for a modulatory role of PHD proteins on synaptic plasticity in the hippocampus. © 2013 Wiley Periodicals, Inc.
Gesehen am 12.05.2021